Overreaction behaviour of syariah compliant stocks in Malaysia / Norli Ali … [et al.] - Ali, Norli; Abd Talib, Norli; Md. Nassir, Annuar; Zainal Abidin, Sazali (Research Management Institute (RMI), 2012)
Studies on overreaction hypothesis on conventional stocks have been vastly documented in previous research (De Bondt and Thaler 1985, 1987; Spyrou et. al 2005; Saleh 2007 and Morad and Salehi 2011, among others). Recently, Morad and Salehi (2011) found that there has been investor's overreaction and it is possible to earn abnormal return by applying the contrarian strategy (inverse investment strategy) in the Tehran stock exchange. In Malaysia, many published works found evidences of overreaction in stock returns such as studied by Hameed and Ting(2000), Ahmad and Hussain (2001) and Lai et al (2003) Norli et al (2009). Although ample evidences have been presented by previous studies mention above, however, there still lack of research in this area on syariah-compliant stocks. It is known that the characteristics of syariah stocks are different from their conventional counterpart in the sense that for firms to be classified as syariah compliant, they need to meet certain regulations or to posses certain features. Questions may arise whether syariah stocks behave like conventional stocks? Do syariah compliant stocks are also the subjects of stock overreaction behavior? Do these stocks able to generate abnormal returns? This study aims to investigate the behavior of syariah compliant stocks with respect to stock overreaction hypothesis.